Bomb Explode Up In The Head And Destroys Thief: The Gangster Style Adirley Queirós Film (Palimpsesto, 2017)
This essay is concerned with analysing the intersection between aesthetic and political elements of hip hop culture originated in Brasilia, Brazilian Federal District, in the movies A cidade é uma só? (2012) and Branco Sai, Preto Fica (2014) the ceilandense director Adirley Queirós. To do this you use references, interviews in blogs and documentaries with the director. At first presents an overview of connections between hip hop culture and the aesthetic and political proposal of the films to subsequently discuss and understand the implications of crossing the mise-en-scène and stylistic director.
Keywords: Film Aesthetics; Hip Hop; Authorship; Mise-En-Scène; Brasilia.